Experimental investigation of subsurface soil water evaporation on soil heat flux plate measurement. (25th January 2016) - Lu, Sen; Ma, Changming; Meng, Ping; Zhang, Jinsong; Zhang, Xiao; Lu, Yili; Yin, Changjun
Highlights: Three methods of soil heat flux measurement were studied. Direct evidence of vapor transfer blockage with the plate method was provided. Needle-type sensors improved soil heat flux measurement accuracy. Abstract: Accurate measurement of soil heat flux is required to describe the heat and mass transfer in soil. In this study, results of soil heat flux derived through the single probe and three needle gradient methods were compared with those obtained via the plate method. Field test was conducted on a bare loamy sand at 1-cm depth and a bare loam at 10-cm depth. Results from the two gradient methods revealed good agreement on flux measurement. The evaporation rate was relatively large on loamy sand, and the flux magnitude measured by the two gradient methods was 1.5 times higher than that of the plate method at 1-cm depth. However, the flux underestimation of the plate method was not observed at 10-cm depth of the bare loam in which the evaporation rate was negligible. Thus, the blockage of vapor transfer from the impervious plates primarily explained the heat flow divergence between the plate and gradient methods. Needle-type sensors exhibited a slight disturbance on the soil over the plate method, which may improve measurement accuracy. Heat flux plates must be placed relatively deep in the soil profile (e.g., 10 cm) to minimize measurement errors.